ZnO nanoparticles produced in the culture supernatant of Bacillus thuringiensis ser. israelensis affect the demographic parameters of Musca domestica using the age‐stage, two‐sex life table. Issue 4 (21st January 2022) - Iqbal, Hafsa; Fatima, Ammara; Khan, Hafiz Azhar Ali
Abstract: BACKGROUND: Indiscriminate use of broad‐spectrum insecticides can have deleterious effects on insects and the environment. The use of nanoparticles synthesized from microbes has recently gained importance as a safe alternative to conventional insecticides. Recently, zinc oxide (ZnO) nanoparticles synthesized using Bacillus thuringiensis have shown insecticidal potential; however, in addition to its acute toxicity, it is necessary to determine possible sublethal effects at the organismal level to understand the toxicity of a new insecticide. Bt ‐derived enzymes such as nitrate reductase and other biomolecules play a vital role in the reduction of metal ions to metal nanoparticles. Here, we assessed the acute toxicity and sublethal effects of ZnO nanoparticles produced in the culture supernatant of B. thuringiensis ser. israelensis ( Bti ) as a reducing agent on the biological traits of Musca domestica . RESULTS: Concentration–response larval bioassays using different concentrations of ZnO‐ Bti ‐supernatant nanoparticles revealed LC10, LC20, LC50 and LC90 values of 4.17, 6.11, 12.73 and 38.90 μg g −1 of larval diet, respectively. Exposure of M. domestica larvae to two concentrations (LC10 and LC20 ) resulted in a lengthened developmental time (egg to adult) and preoviposition period, and reduced fecundity, survival, longevity and oviposition period. Furthermore, population parameters including net reproductive rate, mean generation time, age‐specific survival rate, fecundity, life expectancy and reproductive values, analyzed following age‐stage and two‐sex life table theory, were significantly decreased after exposure to these concentrations of ZnO‐ Bti ‐supernatant nanoparticles compared with the control. CONCLUSION: ZnO‐ Bti ‐supernatant nanoparticles were shown to be toxic to M. domestica . Exposure of M. domestica to low concentrations of ZnO‐ Bti ‐supernatant nanoparticles resulted in negative transgenerational effects on progeny production in this fly. © 2022 Society of Chemical Industry. Abstract : We report acute toxicity and sublethal effects of ZnO nanoparticles produced in the culture supernatant of Bacillus thuringiensis ser. israelensis on biological traits of Musca domestica . Moreover, exposure of M. domestica with sublethal concentrations of nanoparticles resulted in negative transgenerational effects on progeny generation.